Thermodynamic modeling of the Hf-N system - Pang, Mengde; Peng, Yingbiao; Zhou, Peng; Du, Yong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Hf-N based alloys have been widely used and studied in the fields of electronic devices and cutting tools industry. A thermodynamic description of this system is essential for further development of these alloys. By means of CALPHAD method, thermodynamic modeling of the Hf-N system was carried out based on the available phase diagram data as well as thermodynamic property data. The Fcc phase is modeled as (Hf, Va)1(N, Va)1 to cover the composition range since the solubility of nitrogen in Fcc phase is reported up to about 52 at.%. A set of self-consistent thermodynamic parameters for the Hf-N system has been obtained. The computed phase diagrams and thermodynamic quantities using the present parameters agree well with the experimental data.